2012
DOI: 10.1103/physrevb.86.195304
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a highly spin-polarized topological surface state in GeBi2Te4

Abstract: Spin polarization of a topological surface state for GeBi 2 Te 4 , the newly discovered three-dimensional topological insulator, has been studied by means of state-of-the-art spin-and angle-resolved photoemission spectroscopy. It has been revealed that the disorder in the crystal has a minor effect on the surface-state spin polarization, which is 70% near the Dirac point in the bulk energy gap region (∼180 meV). This finding promises not only to realize a highly spin-polarized surface-isolated transport but al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 46 publications
(81 reference statements)
4
24
0
Order By: Relevance
“…[21][22][23][24] Very recently, GBT was claimed to be a 3D TI based on ARPES measurements, 25 albeit with a Dirac point lying below the Fermi energy ( −0.2 eV). This is in contrast with first principle calculations, 25,26 which place the Dirac point inside the band gap, and a resolution of this point is imperative.…”
Section: Introductionmentioning
confidence: 83%
“…[21][22][23][24] Very recently, GBT was claimed to be a 3D TI based on ARPES measurements, 25 albeit with a Dirac point lying below the Fermi energy ( −0.2 eV). This is in contrast with first principle calculations, 25,26 which place the Dirac point inside the band gap, and a resolution of this point is imperative.…”
Section: Introductionmentioning
confidence: 83%
“…102,119) However, a follow-up work by Okamoto et al showed that GeBi 2 Te 4 is naturally electron doped. 120) The GeBi 2 Te 4 crystals grown in the present author's laboratory are also highly conducting with n-type carriers.…”
Section: Three-dimensional Tismentioning
confidence: 99%
“…Many of these compounds have been synthesized and ARPES Neupane et al 2012;Zhang, Chang, Zhang, et al 2011;Eremeev, Landolt, et al 2012;Okamoto et al 2012) and transport measurements (Xiong et al 2012;Taskin et al 2011;Ren et al 2010) are available. Theoretically predicted single surface Dirac cones have been observed in several of these materials via ARPES as well as pump-probe spectroscopy of unoccupied surface states.…”
Section: Ivb 3 Ternary Tetradymites Gembi2nte(m+3n) Seriesmentioning
confidence: 99%